Complete and Incomplete Genome Packaging of Influenza A and B Viruses - Sumiho Nakatsu (American Society for Microbiology, 2016)
ABSTRACT The genomes of influenza A and B viruses comprise eight segmented, single-stranded, negative-sense viral RNAs (vRNAs). Although segmentation of the virus genome complicates the packaging of infectious progeny into virions, it provides an evolutionary benefit in that it allows viruses to exchange vRNAs with other strains. Influenza A viruses are believed to package their eight different vRNAs in a specific manner. However, several studies have shown that many viruses are noninfectious and fail to package at least one vRNA. Therefore, the genome-packaging mechanism is not fully understood. In this study, we used electron microscopy to count the number of ribonucleoproteins (RNPs) inside the virions of different influenza A and B virus strains. All eight strains examined displayed eight RNPs arranged in a “7+1” configuration in which a central RNP was surrounded by seven RNPs. Three-dimensional analysis of the virions showed that at least 80% of the virions packaged all eight RNPs; however, some virions packaged only five to seven RNPs, with the exact proportion depending on the strain examined. These results directly demonstrate that most viruses package eight RNPs, but some do indeed package fewer. Our findings support the selective genome-packaging model and demonstrate the variability in the number of RNPs incorporated by virions, suggesting that the genome-packaging mechanism of influenza viruses is more flexible than previously thought. IMPORTANCE The genomes of influenza A and B viruses contain segmented RNAs, which complicates genome packaging but provides the evolutionary advantage of allowing the exchange of individual genome segments with those of other strains. Some studies have shown that influenza A viruses package all eight genome segments in a specific manner, whereas others have shown that many virions are noninfectious and fail to package at least one genome segment. However, such viruses have never been directly observed. Here, we used electron microscopy to provide the first direct visual evidence of virions packaging an incomplete set of ribonucleoproteins. The percentage of these noninfectious virions varied from 0 to 20, depending on the virus strain, indicating that most virions package all eight genome segments. These results extend our knowledge about how infectious and noninfectious virions coordinate for successful virus infection.